Entoloma griseofibrillosus (Entolomataceae, Basidiomycota), a new species from Punjab, Pakistan - Izhar, Aiman; Qasim, Tayyaba; Asif, Muhammad; Niazi, Abdul Rehman; Khalid, Abdul Nasir (Phytotaxa, 2023)
A new species belonging to the Rusticoides clade of Entoloma, with an omphalinoid habit is described from Pakistan with detailed morphological descriptions, illustrations and molecular data. Illustrations of microcharacteristics and comparison with closely allied species are provided. Entoloma griseofibrillosus is distinguished based on a greyish brown, hygrophanous fibrillose pileus, sub-isodiametric angular spores, varying shapes of cheilocystidia and a pileipellis as a cutis. Phylogenetic estimation based on nrITS and nrLSU regions with a well-nested position of the described taxon is presented in the current study.